2015
DOI: 10.5897/ijeaps2014.0371
|View full text |Cite
|
Sign up to set email alerts
|

The Nigeria education system and vision 20: 2020: A critical development planning perspective

Abstract: The study examines the call for Nigeria becoming one of the twenty most developed economies by the year 2020, as it relates to development planning in Nigeria using the educational system as a unit of analysis. It aims at examining the relevance of this call within the context of existing facilities in the Nigeria educational system both-material and human from the point of view of academic planning. It adopts a historical research methodology of analysis using purely secondary data drawn from statutory docume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Unmet 33 percent is Nigeria's unemployment rate in 2022 *As posited by: (Inegbenebor et al, 2018;Ayodele et al, 2013;Ojo, 2012;Sanubi and Akpotu, 2015).…”
Section: Unemploymentmentioning
confidence: 99%
“…Unmet 33 percent is Nigeria's unemployment rate in 2022 *As posited by: (Inegbenebor et al, 2018;Ayodele et al, 2013;Ojo, 2012;Sanubi and Akpotu, 2015).…”
Section: Unemploymentmentioning
confidence: 99%
“…However, the responsibility for the quality of the teaching and learning and the support of learners often rests with the educators (Olcott & Wright, 1995) and when a number of people are involved in bringing a course to fruition; educators often need to assume responsibility for managing the project. Team leadership demands placed on educators require diverse organizational skills, fostering of a collegial atmosphere, and the establishing of ownership of outcomes and final responsibilities (Franklins et al, 2015;Kelly, 1990). Key to the success of learning and working with the technologies is the ability to work and learn from a network of specialists within a support structure.…”
Section: Systems View: Working Together To Use Technologymentioning
confidence: 99%
“…Furthermore, according toWahab (2002) world bank reported that Ghana allocated 23.81% of its national budgets to education in2015, 22.09% in 2016, 120.1% in 2017 and 18.6% in 2018 Africa, it has kept increasing allocations to the education sectors to the education sector from R246 billion or 16.7% in 2018, R310 billion in 2019, R310billion in 2019, R387billion in 2020 and projected that it will hit R416billion by 2023/2024.From the above analysis, it shows that a little percentage of total expenditure in tertiary institutions goes to capital expenditure which is quite inadequate to cover essentially infrastructural projects like lecture theatres, hostels and other learning facilities. Despite the intervention from Tertiary Education Fund (TETFUND).…”
mentioning
confidence: 99%